Building back normal? An investigation of practice changes in the charitable and on-the-go food provision sectors through COVID-19. Issue 1 (9th December 2022) - Hirth, Steffen; Oncini, Filippo; Boons, Frank; Doherty, Bob
Abstract: The COVID-19 pandemic has brought about debates on rethinking food and other socio-technical systems. While swiftly re-establishing normality has understandable appeal in a crisis, the landscape-level changes during the pandemic also hold windows of opportunity to "build back better" and to achieve sustainability transitions. In this article, we ask whether a cycle of disruption and adaptation results either in the rise of more sustainable niche practices or the consolidation of the socio-techntheorical regimes in place. To approach this question, we consider the specific cases of charitable and on-the-go food provision and examine the extent to which COVID-induced adaptations have resulted in debates about, and implementations of, more just and sustainable practices. We draw on systems transitions and practice theoretical approaches to elucidate dynamics and elasticity and thus the effect of socio-technical practice changes. After describing the pre-COVID food regimes, we evaluate organizational practice adaptations during the lockdowns with regard to (1) changing cultural images of food security and provision, (2) socio-technical innovations, and (3) new forms of governance. We find that rather than justifying the public and policy frame of "building back better, " the effect of recovery measures reinforces the socio-technical regimes and omits wider sectoral and societal sustainability challenges such as the systemic reduction of poverty and waste.